S100β-Positive Cells of Mesenchymal Origin Reside in the Anterior Lobe of the Embryonic Pituitary Gland - Horiguchi, Kotaro (PLoS One, 2016)
The anterior and intermediate lobes of the pituitary gland develop through invagination of the oral ectoderm and as they are endocrine tissues, they participate in the maintenance of vital functions via the synthesis and secretion of numerous hormones. We recently observed that several extrapituitary cells invade the anterior lobe of the developing pituitary gland. This raised the question of the origin(s) of these S100β-positive cells, which are not classic endocrine cells but instead comprise a heterogeneous cell population with plural roles, especially as stem/progenitor cells. To better understand the roles of these S100β-positive cells, we performed immunohistochemical analysis using several markers in S100β/GFP-TG rats, which express GFP in S100β-expressing cells under control of the S100β promoter. GFP-positive cells were present as mesenchymal cells surrounding the developing pituitary gland and at Atwell's recess but were not present in the anterior lobe on embryonic day 15.5. These cells were negative for SOX2, a pituitary stem/progenitor marker, and PRRX1, a mesenchyme and pituitary stem/progenitor marker. However, three days later, GFP-positive and PRRX1-positive (but SOX2-negative) cells were observed in the parenchyma of the anterior lobe. Furthermore, some GFP-positive cells were positive for vimentin, p75, isolectin B4, DESMIN, and Ki67. These data suggest that S100β-positive cells of extrapituitary origin invade the anterior lobe, undergoing proliferation and diverse transformation during pituitary organogenesis.